Nicotinamide phosphoribosyltransferase/visfatin expression by inflammatory monocytes mediates arthritis pathogenesis. Issue 10 (12th January 2013) - Présumey, Jessy; Courties, Gabriel; Louis-Plence, Pascale; Escriou, Virginie; Scherman, Daniel; Pers, Yves-Marie; Yssel, Hans; Pène, Jérôme; Kyburz, Diego; Gay, Steffen; Jorgensen, Christian; Apparailly, Florence
Abstract : Objectives: Nicotinamide phosphoribosyltransferase (NAMPT)/pre-B-cell colony-enhancing factor/visfatin exerts multiple functions and has been implicated in the pathogenesis of rheumatoid arthritis. To gain insight into its role in arthritis and given that NAMPT is identified as a novel mediator of innate immunity, we addressed the function of monocyte-derived NAMPT in experimental arthritis by selective gene knockdown in inflammatory monocytes. Methods: siRNA uptake and NAMPT expression were determined in Ly6C high and Ly6C low monocyte subsets following intravenous injection of siRNA against NAMPT (siNAMPT) or non-targeting siRNA (siCT) formulated with the DMAPAP cationic liposome into mice. Mice with established collagen-induced arthritis (CIA) were treated weekly after disease onset with siNAMPT or siCT and clinical features were assessed. T-helper cell frequencies, cytokine production and percentage of IL-6-producing Ly6C high monocytes were analysed. Using a co-culture system consisting of purified CD14 monocytes and autologous CD4 T cells, NAMPT and cytokine production, and the percentage of IL-17-producing CD4 T cells, were determined following transfection of CD14 monocytes with siCT or siNAMPT. Results: On intravenous injection, siRNA was preferentially engulfed by Ly6C high monocytes, and siRNA-mediated silencing of NAMPT expression in Ly6C high monocytes inhibited CIA progression. This effect was associated with reduced IL-6 production by Ly6C high monocytes, reduced proportion of Th17 cells and autoantibody titers, and decreased activation and infiltration of monocytes/macrophages and neutrophils in arthritic joints. Moreover, NAMPT-RNAi-silenced CD14 monocytes were found to reduce the percentage of IL-17-producing CD4 T cells in vitro. Conclusions: Our results show that the expression of NAMPT in Ly6C high monocytes promotes many downstream effects involved in inflammatory arthritis and demonstrate the utility of targeting disease-causing genes, such as NAMPT, in Ly6C high monocytes for therapeutic intervention in arthritis.